Glucose Detection Using a Surface Plasmon Resonance Biosensor Functionalized by Glucose Oxidase - Atikah Qonitah; Arief Udhiarto; Sabar Pambudi; Ratno Nuryadi; Lia Aprilia (BRIN Publishing (Penerbit BRIN), 2026)
Surface plasmon resonance (SPR) is a well-established optical method for biosensing, allowing real-time monitoring of biomolecular interactions without the need for labeling. In this study, an SPR biosensor was designed for glucose detection by modifying a gold thin film with a self-assembled monolayer (SAM) of 16-mercaptohexadecanoic acid (16-MHA). The SAM layer was chemically activated using (1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride /N-hydroxysuccinimide (EDC/NHS), enabling covalent attachment of glucose oxidase (GOx) for selective interaction with glucose molecules. The sensor was tested with glucose solutions at various concentrations (100–300 mM) and corn syrup, which contains both glucose and fructose, to evaluate selectivity. Detection relied on measuring shifts in the resonance angle of the attenuated total reflection curve, which reflects changes in the local refractive index. The sensor exhibited a clear linear correlation between glucose concentration and resonance angle shift, indicating high sensitivity. In contrast, corn syrup produced much smaller shifts, confirming the selectivity of the biosensor due to GOx’s specificity for β-D-glucose. Performance evaluation showed higher sensitivity (S), narrower full width at half maximum (FWHM), and superior figure of merit (FOM) for glucose compared to corn syrup. These results highlight the potential of SPR for reliable and selective glucose detection in biomedical fields.